THE OBLIQUE FACIAL CLEFT—A REPORT OF 4 CASES - RAJENDRA NATH SHARMA (Indian Journal of Plastic Surgery)
The oblique facial clefts are quite rare. 4 such cases are being presented in this paper alongwith review of the literature.